A Splash and a Crowd: Do Water Fountains and Storefronts Improve Plaza's Visitability?. Issue 9 (November 2022) - Abdulkarim, Dina; Nasar, Jack L.
Whyte made recommendations based on observational studies on making public plazas more livable. The present paper describes two experiments that looked at whether two design attributes he identified—water features and active streets—increase livability measured through visitability, a concept that replaced livability. The studies manipulated four scenarios for fountains (accessible, inaccessible, floor, nothing) and two for storefronts (present, absent) using slides of three plazas each manipulated to present one of the eight scenarios. Study 1 had 66 college students (34 women, 32 men). Study 2 had 93 participants (53 women, 39 men, 1 other) rate the slides on the Perceived Visitability Scale. Fountains and storefronts increased visitability. Accessible water improved visitability for people between the ages 25 and 44. Participants between 18 and 24 and those 45 and older judged plazas with floor fountains as less visitable, suggesting varying effects of certain design elements across age groups.